1998
DOI: 10.1038/sj.leu.2401229
|View full text |Cite
|
Sign up to set email alerts
|

Biologic heterogeneity in Philadelphia chromosome-positive acute leukemia with myeloid morphology: the Eastern Cooperative Oncology Group experience

Abstract: Evaluable karyotypes were available in 776 of 1148 adult patients who were entered on acute myeloid leukemia (AML) treatment protocols of the Eastern Cooperative Oncology Group. Among these, we found seven patients (0.9%) with t(9;22)(q34;q11), the Philadelphia (Ph) chromosome, in bone marrow metaphases. All fulfilled the FAB criteria for AML (three M0, two M1, two M2), although one patient presented with an additional, distinct lymphoid blast cell population. Chromosomal aberrations in addition to the Ph chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 24 publications
1
62
1
Order By: Relevance
“…236,237 Cases with de novo AML carrying BCR/ABL are most often positive for CD13, CD18 and HLA-DR. Expression of B cellrelated antigens is frequent.…”
Section: Bcr/abl Pos Amlmentioning
confidence: 99%
See 1 more Smart Citation
“…236,237 Cases with de novo AML carrying BCR/ABL are most often positive for CD13, CD18 and HLA-DR. Expression of B cellrelated antigens is frequent.…”
Section: Bcr/abl Pos Amlmentioning
confidence: 99%
“…Expression of B cellrelated antigens is frequent. 170,236,238 Potentially important information regarding the pathogenesis of BCR/ABL pos leukemia comes from case reports. A patient with Philadelphia chromosome (Ph)-positive acute mixed-lineage leukemia that expressed both major and minor BCR/ABL mRNA transcripts has been described.…”
Section: Bcr/abl Pos Amlmentioning
confidence: 99%
“…5 This immaturity is usually reflected immunophenotypically; many cases exhibit markers of poorly differentiated AML (CD11b þ , low expression of CD65 and absence of CD14 and CD15), usually coexpressed with lymphoid-associated markers (CD10, CD19, CD20, Cd7 and terminal deoxynucleotidyl transferase (TdT)), suggesting leukemic transformation of a primitive myeloid/lymphoid stem cell. 4 In this report, the blasts were initially negative for CD19, but subsequently showed partial coexpression of CD19 upon demonstration of the Ph chromosome. Second, Ph-positive AML cases have higher initial WBC counts and poorer responses to conventional induction chemotherapy than Ph-negative AML cases.…”
mentioning
confidence: 55%
“…4 Whether cases of Ph-positive AML represent a distinct clinical entity or rather undiagnosed cases of CML in blast phase has been controversial, although most authors contend that Ph-positive AML is a bona fide entity. 4,5 Several observations support this notion. First, although most FAB subtypes may present with the Ph chromosome, these cases tend to demonstrate a high degree of immaturity and present as M0, M1 or M2 subtypes.…”
mentioning
confidence: 99%
“…Ph ? AML constitute \1 % of newly diagnosed cases of AML [9,10] and presence of basophilia in such cases has rarely been reported. Igarashi et al [6] reported a case with similar findings, where blasts harboring minor bcr-abl chimeric mRNA showed basophilic differentiation.…”
Section: Dear Editormentioning
confidence: 99%